THE REPRESENTATION OF MADURESE ISLAM ON YOUTUBE: SEMIOTICS ANALYSIS ON THE COMEDY SHOW 'DHE'REMMAH CONG' - Aditya Fahmi Nurwahid; Citra Safira (Jurnal Sosiologi Reflektif, 2023)
Madurese Islam is one of the cultural treasures of Islam in Indonesia. Madurese culture is intimately intertwined with Islam and reflects diverse perspectives on matters of politics, society, culture, and economics. The emergence of new media has resulted in the digitalization of Madurese Islam, exemplified by its presence on the Tretan Universe YouTube channel. The objective of this study is to provide a semiotic analysis of the Madurese Islamic da'wah content portrayed in the satirical comedy show "Dhe'remmah Cong" featured on the Tretan Universe YouTube channel. This research was carried out using a qualitative approach using the ethnography methodology. Data for this study was gathered through a combination of dialogue narratives and netizen comments obtained from two episodes of the "Dhe'remmah Cong" comedy series. The data was strengthened through literature studies and further analyzed using Charles Sanders Pierce's semiotics. The findings indicated that the "Dhe'remmah Cong" comedy series served as a platform for cultural acculturation between Islam and Madurese culture. Thus, in the subsequent phase, the Madurese Islamic identity can be disseminated into a novel cultural sphere familiar to the Indonesian populace via this YouTube channel.Salah satu khasanah budaya lokal yang dimiliki Islam di Indonesia adalah Islam Madura. Nilai budaya Madura sangat dekat dengan Islam dan mengekspresikan berbagai sudut pandang isu politik, sosial, budaya, atau ekonomi. Perkembangan new media saat ini telah membawa Islam Madura ke dalam platform digital, salah satuya melalui channel Youtube Tretan Universe. Penelitian ini bermaksud untuk menjelaskan analisis semiotika dalam konten dakwah Islam Madura yang ditampilkan dalam komedi satir bertajuk 'Dhe’remmah Cong' di channel Youtube Tretan Universe.  Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif melalui metode netnografi. Teknik pengumpulan data dilakukan dengan penelusuran 2 (dua) seri komedi 'Dhe’remmah Cong' berupa narasi dialog dan komentar netizen. Data diperkuat melalui kajian pustaka dan selanjutnya dianalisis menggunakan semiotika Charles Sanders Pierce. Hasil penelitian mengungkapkan bahwa serial komedi ini menjadi ruang akulturasi budaya dalam Islam dan budaya Madura. Sehingga pada tahap selanjutnya, melalui channel youtube ini, identitas Islam Madura ini dapat menyebar menjadi budaya baru yang dikenal publik Indonesia.